Iraq Economic Monitor, Fall 2019 : Turning the Corner - Sustaining Growth and Creating Opportunities for Iraq’s Youth - World Bank (World Bank, Washington, DC, 2019)
The Iraq Economic Monitor provides an update on key economic developments and policies over the previous six months and presents findings from recent World Bank work on Iraq, placing them in a longer-term and global context and assessing the implications of these developments and other changes in policy regarding the outlook for Iraq. Its coverage ranges from the macroeconomy to business environment and private sector development. It is intended for a wide audience, including policy makers, business leaders, financial market participants, and the community of analysts and professionals engaged in Iraq.